113 Impact of the HOP-STEP program in improving provider knowledge and skills for lupus pregnancy planning and management. (April 2019) - Njagu, Ravyn S; Eudy, Amanda M; Snyderman, Amanda; Criscione-Schreiber, Lisa G; Clowse, Megan EB
Abstract : Background: The HOP-STEP Program (Healthy Outcomes in Pregnancy with SLE through Education of Providers) is designed to optimize lupus pregnancy outcomes through providing physicians with the necessary knowledge, skills and resources to guide pregnancy planning and management. The goal of this analysis was to measure the impact of the HOP-STEP program. Methods: The in-person component of HOP-STEP was presented at the Association of Women in Rheumatology (AWIR) Conference in August 2018. The workshop included a presentation, peer roll-playing workshop, patient simulation, and distribution of Preparing for Pregnancy Checklist and Birth Control for Women with Lupus handouts. A survey was emailed to 149 individuals before and after workshop completion. Results: The analysis included 68 pre-surveys (response rate 46%, 93% women, 66% attending-level rheumatologists) and 55 post-surveys (response rate 37%, 95% women, 62% attending-level rheumatologists). Systematic approach: After the program, more providers had a systematic approach to preparing a woman with lupus for pregnancy (45.6% to 94.6%; p<0.0001). Contraception: There was an increase in correct responses regarding emergency contraception (47% to 91%, p<0.0001); a decrease in correct responses regarding IUD use (96% to 77%, p=0.003); and no difference in correct responses to questions regarding thrombotic risk or efficacy of contraception. Teratogenicity: After the program, fewer providers identified pregnancy-compatible medications (azathioprine and tacrolimus) as teratogenic (60% to 9%; p<0.0001). Additionally, more providers identified all three teratogenic medications (methotrexate, mycophenolate, and cyclophosphamide) (80.9% to 92.7%; p=0.07). Birth Defects: Participants were asked to put medications in order from most to least likely to cause birth defects, the correct order being mycophenolate or cyclophosphamide, methotrexate, then leflunomide. No difference was observed in correctly ordered medications (16.2% to 16.4%; p=1.0). However, there was an increase in providers who correctly identified mycophenolate as the most or second-most teratogenic (13% to 44%; p=0.02). Provider Confidence: Participants were asked to rank their confidence on a scale of 0 (not confident) to 100 (very confident). Median provider confidence increased for helping women with lupus choose appropriate contraception (59 to 89; p<0.0001) and medications compatible with pregnancy (66 to 91; p<0.0001). Conclusions: After participation in the in-person HOP-STEP program, providers had increased knowledge and confidence in pregnancy planning and management in lupus patients. The program emphasized skills over knowledge, as is reflected in the survey results. The handouts used in the program provide all of the necessary information, which can overcome existing and ongoing gaps in rheumatologists knowledge. Funding Source(s): GlaxoSmithKline